Advanced Transition Preemption Strategy for Signalized Intersections near Highway-Rail Grade Crossings with Dual Tracks - Yifeng Chen; Laurence R. Rilett; Zifeng Wu (Journal of Advanced Transportation)
The current preemption method for traffic signals at intersections located near highway-rail grade crossings (IHRGC) is known as the standard preemption (SP). The SP strategy is designed to give priority to the phases which clear vehicles off the railroad tracks as quickly as possible before a train arrives at HRGCs and provides the drivers and pedestrians with a minimum warning time (MWT). However, the SP considers neither pedestrian safety nor system efficiency at IHRGCs. As a result, this may lead to safety and delay problems at IHRGCs. To solve the problems, a state-of-the-art transition preemption strategy (TPS) algorithm, named TPS_DT, is developed in this paper. The new TPS algorithm is designed for corridors with multiple HGRCs that have dual tracks. An urban highway corridor with multiple HRGCs in Lincoln, NE, was selected as the study corridor. A calibrated VISSIM model of the study corridor was used to test the safety and efficiency of the proposed algorithm. The algorithm was coded in VAP, which is an add-on module of VISSIM. A roadway-railway corridor with multiple IHRGC and dual rail tracks in Lincoln, NE, was used as the testbed. The Measurements of Effectiveness (MOEs) used for evaluation include the rate of pedestrian phase cutoffs, intersection vehicle delay, and corridor vehicle delay. It was found that TPS_DT can significantly improve pedestrian safety and reduce vehicle delay at IHRGCs. Furthermore, the effects of train arrival prediction errors on safety and efficiency of the IHRGCs are also analyzed in the paper.